Length-weight relationship and relative condition factor in Daysciaena albida (Cuv.) and Gerres filamentosus (Cuv.) - Samuel, C.T., Kurup, B.M. and (Fishery Technology, 2021)
The length-weight relationship of Daysciaena albida and Gerres filamentosus were calculated separately for indeterminants, mature males and mature females. The logarithmic regression equation obtained for D. albida - males: log w = -1.5055 + 2.8618 log l; females: log w = -0.9260 + 2.4089 log l; indeterminants: log w = -l.7188 + 3.0616 log l. The regression co-efficients between males and females, males and in determinants and female and in determinants showed significant differences. In G. filamentosus the relationship can be expressed as males: log w = -1.3224 + 2.8740 log 1; females: log w = -1.2874 + 2.8381 log l; indeterminants: log w = -0.8167 + 2.2558 log l. The difference in regression co-efficients between male and female are insignificant at 5% level whereas significant differences were observed between males and indeterminants and females and indeterminants. The relative condition factor (Kn) was calculated for the above two species. In D. albida the reasons for the fluctuations of Kn values can be attributed to both spawning cycle as well as feeding intensity whereas in G. filamentosus it synchronies mainly with spawning cycle.